INOVASI RESEP KUDAPAN RENDAH KARBOHIDRAT BERBASIS PANGAN LOKAL SEBAGAI SOLUSI PENCEGAHAN OBESITAS DI DAERAH KOTA TANGERANG - Paundrianagari, Meilita Dwi; Amir, Chindy; Piliang, Marzuki (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2024)
Obesity is a growing global health problem, including in Indonesia. The prevalence of adult obesity in Indonesia reached 23.4% in 2023, demonstrating the urgency of healthy food-based interventions (Ministry of Health of the Republic of Indonesia, 2023; ([www.jpnn.com][1])). A high-carbohydrate, low-fiber diet is a major contributing factor to the increase in obesity, particularly in urban areas such as Tangerang City. This study aims to develop innovative low-carbohydrate snacks based on local foods as an alternative to obesity prevention. The method used was an experimental study with a recipe formulation approach using local ingredients such as modified cassava flour, nuts, and high-fiber vegetables. The results showed that the developed low-carbohydrate snacks have a lower energy content and more balanced nutritional value than conventional snacks. Furthermore, this innovation has the potential to be accepted by the community because it uses familiar and economical local ingredients. Thus, the development of healthy snacks based on local foods can be a preventive strategy to reduce the prevalence of obesity in Tangerang City.